AMEE Guide No. 123 – How to read studies of educational costs. (4th May 2019) - Maloney, S.; Cook, D. A.; Golub, R.; Foo, J.; Cleland, J.; Rivers, G.; Tolsgaard, M. G.; Evans, D.; Abdalla, M. E.; Walsh, K.
Abstract: Healthcare and health professions education share many of the same problems in decision making. In both cases, there is a finite amount of resources, and so choices need to be made between alternatives. To navigate the options available requires effective decision making. Choosing one option requires consideration of its opportunity cost – the benefit forgone of the other competing options. The purpose of this abridged AMEE guide is to introduce educational decision-makers to the economic concept of cost, and how to read studies about educational costs to inform effective cost-conscious decision-making. This guide leads with a brief review of study designs commonly utilized in this field of research, followed by an overview of how study findings are commonly presented. The tutorial will then offer a four-step model for appraising and considering the results of an economic evaluation. It asks the questions: (1) Can I trust the results? (2) What are the results telling me? (3) Could the results be transferred to my context? (4) Should I change my practice?